STRATEGY FOR COLLECTING LAND AND BUILDING TAX BY THE GOVERNMENT OF CAMPAKA VILLAGE CIGUGUR DISTRICT PANGANDARAN REGENCY - Rissa Dwi Meilani; Agus Nurulsyam Suparman; Kiki Endah (JGSRD: Journal of Government Science and Rural Development, 2023)
This research is motivated by the not yet optimal strategy of collecting land and building taxes by the Campaka Village Government, Cigugur District, Pangandaran Regency. The purpose of this study was to determine the strategy of collecting land and building taxes by the Campaka Village Government, Cigugur District, Pangandaran Regency. The method used in this research is descriptive analysis. There are 7 informants. Data collection techniques are library research, field studies (observations and interviews) and documentation. The author uses qualitative data analysis techniques through processing data from interviews and observations to draw conclusions so that they can answer the problems in the study. Based on the results of the study, it is known that the strategy for collecting land and building taxes by the Campaka Village Government, Cigugur District, Pangandaran Regency has not been implemented properly in accordance with the basic elements in the strategic management process according to Sedarmayanti (2014: 24). This is because there are still problems encountered in the process of collecting land and building taxes, such as the lack of awareness of taxpayers in paying land and building taxes, in addition to the lack of taxpayers outside the village who pay attention to paying land and building taxes so that the largest arrears come from taxpayers. outside the village caused by the obstacles faced by land and building tax collectors due to the lack of awareness of taxpayers both inside the village and outside the village in paying taxes on time. Therefore, PBB collectors have tried to approach taxpayers to communicate so that officers understand the problems faced by taxpayers in addition to evaluating PBB revenues so that problems in collecting PBB can be identified.